Use of Chitosan to Prevent Aeromonas hydrophila Infection on Catfish Clarias sp. - Sukenda, .; Jamal, L.; Wahjuningrum, D.; Hasan, A. (Jurnal Akuakultur Indonesia, 2008)
Immunostimulation effect of chitosan against motile aeromonas septicemia caused by Aeromonas hydrophila were examined in catfish (Clarias sp.). Experimental fish were injected with 2, 4 and 6 μg/g fish of chitosan.  All fish were subsequently challenged by 105 CFU/ml of live A. hydrophila by injection method.  Negative control injected with PBS and positive control injected with only A. hydrophila were included in the experiment. Results showed that total count of eritrocyte, leucocyte,  level of hematocrite, haemoglobin and phagocytic index higher at fish injected with chitosan previously compared with control as well as lymphocyte, neutrophile, monocyte, and trombocyte.  Either survival rate or growth  of fish injected with chitosan were found to increase in accordance with dose of chitosan. Kata Kunci : chitosan, Aeromonas hydrophila, immunostimulant, Clarias sp.   ABSTRAK Efek imunostimulasi dari kitosan melawan Motile Aeromonad Septicemia yang disebabkan oleh A. hydrophila dilihat pada ikan lele (Clarias sp.). Ikan uji disuntik dengan larutan kitosan dengan dosis  2, 4 and 6 μg/g, yang selanjutnya diuji tantang dengan bakteri  A. hydrophila 105 CFU/ml melalui penyuntikan intramuskular.  Kontrol negative disuntik dengan PBS dan control positif disuntik hanya dengan bakteri  A. hydrophila disertakan dalam penelitian ini. Hasil menunjukkan bahwa jumlah eritrosit, lekosit, level hematokrit, hemoglobin dan indeks fagositik lebih tinggi pada ikan-ikan yang diberi kitosan sebelumnya dibandingkan dengan tanpa pemberian kitosan sebelumnya.  Begitu pula dengan kadar limfosit, netrofil, monosit dan trombosit.  Sintasan dan pertumbuhan ikan yang diberi kitosan meningkat sejalan dengan dosis kitosan yang diberikan. Kata kunci: kitosan, Aeromonas hydrophila, immunostimulan, Clarias sp.